Pisarstwo prymasa Andrzeja Olszowskiego (1623–1677): The writing of primate Andrzej Olszowski (1623–1677) - Wichowa, Maria (Prace Polonistyczne, 2019)
Primate Andrzej Olszowski (1623–1677) left a rich literary legacy, which has not yet become an object of interest for historians of literature. Olszowski’s works have been treated as source texts for political history studies of the Polish-Lithuanian Commonwealth in the 17th century. The first part of the article is an outline of Olszowski’s biography, secondly, the entire output of the writer is briefly summarized. Next, the main work of Olszowski: Censura candidatorum sceptri polonici is analyzed thoroughly – both in terms of issues and writing skills. Also, the treatise De Archiepiscopatu Gnesnensi receives insightful analysis. Other works, especially oratorical texts, have been discussed synthetically, but with regard to the literary qualities of these texts, with an indication of Olszowski’s mastery of the art of rhetoric. In addition, the outline of the entire work of the Primate is concisely drawn, postulating that it should become the subject of a monographic study.